Assessment of Islamic Religious Learning in the Perspective of Islamic Educational Psychology - Asman Asman; Muliani Muliani; Amin Amin (Early Publishing, 2025)
Assessment must be considered as one of the key factors in determining the success of a presentation or structure and learning outcomes, not just as a model for evaluating learning outcomes. Assessment activities should inform Islamic religious education teachers or educators to improve teaching skills and enable students to achieve ideal learning development. Educators play a very important role in determining the quality of instruction provided. This is important whether you're planning learning through design science or learning plans, or during the evaluation phase. Islamic religious educators can make good assessments, but they need correct data. Correct information can only be obtained by using standardized inspection items. Evaluation is necessary for early detection, which is an effort and the first step in intervening in child development. It therefore seems impossible to measure quality of life by evaluating a specific list of (objective) factors. This type of research uses fieldwork or field research. Data collection techniques were conducted using in-depth interviews based on interview guides and were unstructured. To perform this qualitative data analysis, several stages and steps should be emphasized: data reduction and information presentation and verification.